Early Complications and Outcomes in Combat Injury–Related Invasive Fungal Wound Infections: A Case–Control Analysis. Issue 3 (March 2016) - Lewandowski, Louis R.; Weintrob, Amy C.; Tribble, David R.; Rodriguez, Carlos J.; Petfield, Joseph; Lloyd, Bradley A.; Murray, Clinton K.; Stinner, Daniel; Aggarwal, Deepak; Shaikh, Faraz; Potter, Benjamin K.
Abstract : Objective: Clinicians have anecdotally noted that combat-related invasive fungal wound infections (IFIs) lead to residual limb shortening, additional days and operative procedures before initial wound closure, and high early complication rates. We evaluated the validity of these observations and identified risk factors that may impact time to initial wound closure. Design: Retrospective review and case–control analysis. Setting: Military hospitals. Patients/Participants: US military personnel injured during combat operations (2009–2011). The IFI cases were identified based on the presence of recurrent, necrotic extremity wounds with mold growth in culture, and/or histopathologic fungal evidence. Non-IFI controls were matched on injury pattern and severity. In a supplemental matching analysis, non-IFI controls were also matched by blood volume transfused within 24 hours of injury. Intervention: None. Main Outcome Measurements: Amputation revision rate and loss of functional levels. Results: Seventy-one IFI cases (112 fungal–infected extremity wounds) were identified and matched to 160 control patients (315 non-IFI extremity wounds). The IFI wounds resulted in significantly more changes in amputation level ( P < 0.001). Additionally, significantly ( P < 0.001) higher number of operative procedures and longer duration to initial wound closure were associated with IFI. A shorter duration to initial wound closure was significantly associated with wounds lacking IFIs (Hazard ratio: 1.53; 95% confidence interval, 1.17–2.01). The supplemental matching analysis found similar results. Conclusions: Our analysis indicates that IFIs adversely impact wound healing and patient recovery, requiring more frequent proximal amputation revisions and leading to higher early complication rates. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.